The Characteristics of Diverticular Disease in Caribbean Population: A Control Group Study - Moana Gelu-Simeon; Matthieu Schnee; Marie-Josée Lafrance; Pauline Plazy-Chabrand; Anne-Sophie Schneck; Georgette Saint-Georges; Marceline Alexis; Stéphanie Delumeau; Philippe Montigny; Roger Faroux; Jérome Dimet; Eric Saillard (Canadian Journal of Gastroenterology and Hepatology)
Background. Diverticulosis is not well characterized in the Caribbeans. Our aim was to compare the anatomical presentation of colonic diverticulosis in African Caribbeans (group AC) versus Europeans (group E) and severity. Methods. We conducted a prospective controlled study involving 274 patients admitted for lower gastrointestinal haemorrhage (LGIH) in France (center 1: Guadeloupe; center 2: La Roche-sur-Yon); 179 cases with diverticular haemorrhage, including 129 in group AC and 40 in group E. Exploration of the colon included a detailed assessment of diverticula using a dedicated endoscopic grid. Results. AC and E had similar characteristics in terms of age, gender, previous history of LGIH, body mass index, dietary habits, and medications, but AC had significantly poorer hemodynamic parameters at admission and required more blood transfusions (66.7% vs. 42.5%; p=0.01) during hospitalization. Out of the 169 patients included in the study, a complete exploration of the colon was achieved in 81% (N = 137) (AC, n = 106; E, n = 31), and revealed right-side diverticulosis in AC (in 90.6%, included into a pancolonic form in 73.6% vs. 35.5%; p=0.0002) and left-side diverticulosis in E (in 96.8%, isolated form in 58.1% vs. 9.4%, p=0.0002). These data were confirmed by a sensitivity analysis using an endoscopic grid in 92 patients, achieving a higher frequency and larger size of diverticula in AC. Conclusion. Our study has shown that diverticulosis was pancolonic in AC and more frequently associated with more severe haemorrhage than the left-sided diverticulosis of Europeans. This anatomical presentation may be driven by the genetic background more than the environment and diet.